2005
DOI: 10.1111/j.1095-8339.2005.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative floral structure and systematics in Crossosomatales (Crossosomataceae, Stachyuraceae, Staphyleaceae, Aphloiaceae, Geissolomataceae, Ixerbaceae, Strasburgeriaceae)

Abstract: Floral structure of all putative families of Crossosomatales as suggested by molecular studies was comparatively studied. The seven comprise Crossosomataceae, Stachyuraceae, Staphyleaceae, Aphloiaceae, Geissolomataceae, Ixerbaceae, and Strasburgeriaceae. The entire clade (1) is highly supported by floral structure, also the clades (in sequence of diminishing structural support): Ixerbaceae/Strasburgeriaceae (2), Geissolomataceae/Ixerbaceae/Strasburgeriaceae (3), Aphloiaceae/Geissolomataceae/Ixerbaceae/Strasbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 95 publications
1
39
1
Order By: Relevance
“…A few perforation plates with a single bar were observed in various places in secondary xylem of Velascoa recondita, but perforation plates are predominantly simple in that species. The number of bars per perforation plate in Stachyuraceae is greater than that reported by Metcalfe and Chalk (1950) or Matthews and Endress (2005).…”
Section: Vessel Elementscontrasting
confidence: 57%
See 3 more Smart Citations
“…A few perforation plates with a single bar were observed in various places in secondary xylem of Velascoa recondita, but perforation plates are predominantly simple in that species. The number of bars per perforation plate in Stachyuraceae is greater than that reported by Metcalfe and Chalk (1950) or Matthews and Endress (2005).…”
Section: Vessel Elementscontrasting
confidence: 57%
“…The rays of Strasburgeriaceae, along with those of Ixerbaceae, might represent an apomorphy by rarely exceeding two cells in width. Because Ixerbaceae and Strasburgeriaceae seem closely related (Matthews and Endress 2005), such rays might represent a synapomorphy, but this feature is not a clearly definable one. The occurrence of unusually wide rays (''rays of two distinct widths'') in Aphloiaceae and Geissolomataceae might also represent apomorphies.…”
Section: Departures From Primitive Character Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of perianth differentiation is linked with the phyllotaxis (spiral or whorled) and number of perianth parts. Based on evidence in Eupomatia, Endress (2003Endress ( , 2005 and Kim et al (2005b) discussed the difference between bracts and tepals in the basal angiosperms as categories with different levels of complexity. Endress demonstrated that the association of bracts (in the form of a calyptra) with tepals, in clades where petals have not yet evolved, could be considered analogous to the formation of sepals and petals.…”
Section: Perianth In the Basal Angiospermsmentioning
confidence: 99%